In-vivo photodynamic therapy studies in cancer - Kaleli, Süleyman; Mazlan, Muhammad Alif; Md Isa, Muhammad Lokman (Hyderabad: Acta Scientific Publications Opc Private Limited, 2021)
The traditional surgical method for cancer treatment has not been successful in removing primary or metastatic tumors. Chemotherapy and radiation therapy methods, as well as cancer cells and healthy cells affect the process of treatment nausea, hair loss, immune system weakness, such as there are many side effects. Photodynamic therapy (PDT) is a regulator for the treatment of many malignant carcinomas that can cause immunogenic apoptosis. Despite these adversities in surgery, chemotherapy and radiation therapy, significant progress has been made in PDT research recently. This review article is aimed to present recent studies.